Poetics of expression image mermaid in oral folk art (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In an article comparative aspect analyses Ukrainian and Russian folk expressive songs, characterized their themed art-shaped features. Indentified their differences and similarities.
Keywords: folklore; genre; shaped structure; expressive songs; mermaid